2014
DOI: 10.1002/cam4.180
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early progression of non‐small‐cell lung cancer treated by epidermal growth factor receptor tyrosine‐kinase inhibitors

Abstract: Epidermal growth factor receptor tyrosine-kinase inhibitors (EGFR-TKI) are a therapeutic option as second-line therapy in non-small-cell lung carcinoma (NSCLC), regardless of the EGFR gene status. Identifying patients with early progression during EGFR-TKI treatment will help clinicians to choose the best regimen, TKI or chemotherapy. From a prospective database, all patients treated with gefitinib or erlotinib between 2001 and 2010 were retrospectively reviewed. Patients were classified into two groups accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(53 reference statements)
0
3
1
Order By: Relevance
“…Research by Rozensztajn et al in Paris showed that age affects PFS of patients. Older age had lower risk of progression by 4% with an OR of 0.96 (95% CI 0.93-0.98, p = 0.005) [16]. Another study by Tsai et al in Taiwan had different results from this study.…”
Section: Discussioncontrasting
confidence: 75%
“…Research by Rozensztajn et al in Paris showed that age affects PFS of patients. Older age had lower risk of progression by 4% with an OR of 0.96 (95% CI 0.93-0.98, p = 0.005) [16]. Another study by Tsai et al in Taiwan had different results from this study.…”
Section: Discussioncontrasting
confidence: 75%
“…One study compared the characteristics of patients who experience early progression with patients whose disease was controlled after receiving erlotinib or gefitinib for at least 7 days, and the univariate analysis results showed that weight loss ≥10% was one of clinical factors associated with early progression 17 . This was the only study reported weight loss was associated with poorer outcome in patients treated with EGFR-TKI.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on dosing and study conditions, erlotinib rash can be seen in 75–90 % of treated patients, being severe in ~10 % (Tan and Chan 2009 ; Jia et al 2009 ; Rozensztajn et al 2014 ) This rash is usually treated with topical antibiotics, meticulous skin care, minocycline and topical steroids (Kiyohara et al 2013 ). Development of an erlotinib rash confers clear but minor overall survival advantage when treating various cancers (Stepanski et al 2013 ; Kaburagi et al 2013 ; Peereboom et al 2010 ; Kiyohara et al 2013 ; Aranda et al 2012 ; Petrelli et al 2012 ; Fiala et al 2013 ) with some indication that greater rash severity is correlated with slightly longer OS than lesser severity rashes (Kiyohara et al 2013 ; Rozensztajn et al 2014 ; Petrelli et al 2012 ) A statistically significant association exists between higher erlotinib levels and greater likelihood of rash (Tiseo et al 2014 ; Fukudo et al 2013 ).…”
Section: The Erlotinib Rashmentioning
confidence: 99%